ChemInform Abstract: A Novel One‐Pot Ionic Liquid Promoted Synthesis of Benzo[a]phenothiazine Derivatives. Issue 23 (June 2015) - Yadav, Ashok K.; Gupta, Manisha
Abstract via condensation reactions of 1, 4‐naphthoquinones (II) with 2‐aminobenzenethiols or their Zn‐salts